2010
DOI: 10.1071/zo10042
|View full text |Cite
|
Sign up to set email alerts
|

Habitat associations of the long-nosed potoroo (Potorous tridactylus) at multiple spatial scales

Abstract: This study examined the coarse-and fine-scale habitat preferences of the long-nosed potoroo (Potorous tridactylus) in the Southern Highlands of New South Wales, in order to inform the management of this threatened species. Live-trapping was conducted in autumn and spring, from 2005 to 2008, at two sites. Macrohabitat preferences were examined by comparing trap success with numerous habitat attributes at each trap site. In spring 2007 and autumn 2008, microhabitat use was also examined, using the spool-and-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…They were also at very low densities before the fire, which was less than 10 years after the previous fire in 1972. Past studies have indicated associations between potoroos and a dense ground layer (Seebeck et al 1989), but a more recent study suggests an association between potoroos and tree canopy cover consistent with the strong positive association we observed (Norton et al 2010). The latter may reflect an association between tree canopy cover and fungi, a preferred food of potoroos (Claridge & May 1994).…”
Section: Discussionsupporting
confidence: 84%
“…They were also at very low densities before the fire, which was less than 10 years after the previous fire in 1972. Past studies have indicated associations between potoroos and a dense ground layer (Seebeck et al 1989), but a more recent study suggests an association between potoroos and tree canopy cover consistent with the strong positive association we observed (Norton et al 2010). The latter may reflect an association between tree canopy cover and fungi, a preferred food of potoroos (Claridge & May 1994).…”
Section: Discussionsupporting
confidence: 84%
“…Smaller animals that are incapable of out running predators are likely to seek refuge in dense habitats to avoid detection and pursuit, particularly when rearing young (Signorell et al, 2010), whereas larger species that are capable of rapid movement have a higher chance of evading predation in more open habitats (Creel et al, 2005). Consistent with previous studies, we found that occupancy of the long-nosed potoroo was influenced strongly by dense ground cover (Claridge & Barry, 2000;Norton et al, 2011) and occupancy of the red-legged pademelon was strongly influenced by areas of open ground cover (Vernes, 1995). The long-nosed potoroo's requirement for dense ground cover over other habitat variables may reflect a need for concealment from terrestrial predators, and habitat for diurnal nesting sites.…”
Section: Habitat and Conservation Reservessupporting
confidence: 89%
“…Tooloom, and Mt Jerusalem).Previous studies have shown that potoroos occupy a broadrange of vegetation communities across their distribution. identified coastal sandy wet heathlands, moist inland woodlands and forests on plateaux and their associated slopes and gullies to be important for potoroos across eastern Australia Norton et al, (2011). We confirm that structural complexity of understory vegetation is critical to this species Claridge, Seebeck, and Rose (2007).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…EVC is a vegetation classification for assessing biodiversity conservation at the landscape scale in Victoria (Department of Sustainability and Environment, 2007) and closely matches habitat descriptions for the three native prey species (Bennett, 1993;Norton et al, 2010;Rees and Paull, 2000). Randomization of treatment and non-treatment areas was not logistically feasible, as all treatment areas were located in the southern half of the study area (Fig.…”
Section: Methodsmentioning
confidence: 99%